2022
DOI: 10.1093/oncolo/oyac227
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Death Among Patients with Advanced Cancer Receiving Early Palliative Care and Their Caregivers: Results from a Mixed-Method Analysis

Abstract: Background Oncologists are often concerned that talking about death with patients may hinder their relationship. However, the views of death held by patients have not been thoroughly investigated. This study aimed to describe the perception of death among patients with advanced cancer receiving early palliative care (EPC) and their caregivers. Material and Methods Qualitative and quantitative analyses were performed on 2 data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As in previous studies, adults tended to look back on their lives and experience more loss and regret, and most adults expressed anxiety, fear, and despair when talking about death. 30,31 In our study, we found that the children had very few thoughts of regret and guilt and showed no apparent fear when talking about death. As previously reported, 32 young children are less likely to understand the permanence of death.…”
Section: What This Study Addsmentioning
confidence: 46%
“…As in previous studies, adults tended to look back on their lives and experience more loss and regret, and most adults expressed anxiety, fear, and despair when talking about death. 30,31 In our study, we found that the children had very few thoughts of regret and guilt and showed no apparent fear when talking about death. As previously reported, 32 young children are less likely to understand the permanence of death.…”
Section: What This Study Addsmentioning
confidence: 46%
“…Arguably, this clinical group has the highest need to access MDT services and models of care and should be urgently prioritised. A further essential consideration is access to early palliative care services in both acute and community settings to optimise hope [ 52 ], normalising the idea of dying [ 53 ] to provide the needed reassurance [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…EPC offers several strategies that caregivers can employ to face mortality and manage their emotional distress. These strategies include providing social support and addressing the topic honestly ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that respondents could answer the questions comfortably and to minimize the risk of social desirability bias in their answers, a self-administered, anonymous questionnaire was chosen over an oral interview. The questionnaire answers have already been analyzed to gather information on the caregiver’s perception of the disease before and after an EPC intervention ( 36 ), the caregiver’s perception of death and hope ( 37 , 38 ), and the caregiver’s feeling of gratitude ( 39 ). For this retrospective study, the answers were reanalyzed.…”
Section: Methodsmentioning
confidence: 99%